Antigen-Presenting Cells in Psoriasis - Dóra Antal; Shahrzad Alimohammadi; Péter Bai; Attila Gábor Szöllősi; Magdolna Szántó (Life, 2022)
Psoriasis is classically considered a chronic inflammatory skin disorder, however the identification of autoantigens in its pathogenesis established it as a T cell mediated autoimmune disease. As such professional antigen-presenting cells (APCs) are key players in the development of lesions. APCs in the skin include dendritic cells, Langerhans cells and monocytes/macrophages. In addition, epidermal keratinocytes and dermal mast cells are also endowed with antigen-presenting capacity. Skin APCs have central role in the maintenance of cutaneous immune homeostasis, as well as in initiating and sustaining inflammation under pathologic conditions. In this review we discuss the functional specialization of human skin APCs that promote T cell activation and adaptive immune response during psoriasis initiation and onset.